1994
DOI: 10.1038/372068a0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of a hammerhead ribozyme

Abstract: The hammerhead ribozyme is a small catalytic RNA motif made up of three base-paired stems and a core of highly conserved, non-complementary nucleotides essential for catalysis. The X-ray crystallographic structure of a hammerhead RNA-DNA ribozyme-inhibitor complex at 2.6 A resolution reveals that the base-paired stems are A-form helices and that the core has two structural domains. The first domain is formed by the sequence 5'-CUGA following stem I and is a sharp turn identical to the uridine turn of transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
904
1
9

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,022 publications
(965 citation statements)
references
References 35 publications
51
904
1
9
Order By: Relevance
“…The 5 nt immediately 59 of the stem are highly conserved, with a consensus of C or A at positions 1 and 2, and adenosines at positions 3, 4, and 5+ We have found that the first two positions can be deleted with no effect on SLBP binding (Fig+ 4)+ They may be conserved as C or A simply to prevent them from forming deleterious base pairs with the conserved C and A residues 39 of the stem+ However, deletion of position 3 had a moderate effect and deletion of position 4 had a strong effect on SLBP recognition+ This suggests that SLBP makes critical contacts at positions 3 and 4+ Alternatively, adenosine residues in general, and multiple adenosine residues in particular, are often found to make tertiary RNA-RNA contacts (Pley et al+, 1994;Cate et al+, 1996;Costa & Michel, 1997;Strobel et al+, 1998), leading to the possibility of a strained base-triple or pseudoknot structure involving A3 or A4+ However, divalent cations are often required for these interactions, whereas here the specificity of the interaction was maintained in the absence of Mg 2ϩ and the presence of EDTA, and SLBP binding in fact was reduced by the presence of MgCl 2 + This makes the possibility of a more complex structure unlikely+ Similarly, the ACCCA sequence 39 of the stem is also highly conserved+ The major position of cleavage by the U7 snRNP is immediately 39 of A26, and efficiency of this cleavage is dependent on SLBP (Streit et al+, 1993;Dominski et al+, 1995)+ These considerations suggested that SLBP may contact the 39 flanking region FIGURE 5. A comparison of the consensus sequence of the histone mRNA 39 stem-loop with the specificity determinants for SLBP recognition+ Shown in gray boxes are nucleotides that show a deleterious effect on SLBP affinity when mutated or deleted+ and orient it for cleavage by the U7 snRNP+ We found, however, that much of the 39 flanking region could be deleted without a large effect on the affinity of the SLBP-RNA interaction (Fig+ 4)+ Deletion of four of the residues had only a slight effect, and deletion of the entire 39 flanking region increased the K d 5+5-fold+ This suggests that SLBP is not making extensive contacts to most of this region, but rather is only interacting with the first A residue 39 of the stem+ Alternatively, the presence of a 39 overhanging adenosine has been shown to contribute approximately 1 kcal/mol to the stability of short oligonucleotide duplexes (Freier et al+, 1986)+ It is possible, therefore, that A22 simply serves to stabilize the stem and is not contacting SLBP+ These data suggest that SLBP may enhance 39-end processing by direct or indirect recruitment of the U7 snRNP to the cleavage site as has been previously proposed (Dominski et al+, 1999), rather than by directly ordering the RNA structure at the cleavage site+ The sequence conservation of the 39 flanking region (and possibly the bottom G-C pair of the stem) may be necessary for the binding of other components of the 39-end processing machinery+ SLBP has no homology with any other proteins thus far discovered+ It contains a relatively small, approximately 73 amino acid, RNA-binding domain predicted to contain three a-helices (Wang et al+, 1996;Martin et al+, 2000)+ Previously characterized RNA-binding domains …”
Section: Discussionmentioning
confidence: 99%
“…The 5 nt immediately 59 of the stem are highly conserved, with a consensus of C or A at positions 1 and 2, and adenosines at positions 3, 4, and 5+ We have found that the first two positions can be deleted with no effect on SLBP binding (Fig+ 4)+ They may be conserved as C or A simply to prevent them from forming deleterious base pairs with the conserved C and A residues 39 of the stem+ However, deletion of position 3 had a moderate effect and deletion of position 4 had a strong effect on SLBP recognition+ This suggests that SLBP makes critical contacts at positions 3 and 4+ Alternatively, adenosine residues in general, and multiple adenosine residues in particular, are often found to make tertiary RNA-RNA contacts (Pley et al+, 1994;Cate et al+, 1996;Costa & Michel, 1997;Strobel et al+, 1998), leading to the possibility of a strained base-triple or pseudoknot structure involving A3 or A4+ However, divalent cations are often required for these interactions, whereas here the specificity of the interaction was maintained in the absence of Mg 2ϩ and the presence of EDTA, and SLBP binding in fact was reduced by the presence of MgCl 2 + This makes the possibility of a more complex structure unlikely+ Similarly, the ACCCA sequence 39 of the stem is also highly conserved+ The major position of cleavage by the U7 snRNP is immediately 39 of A26, and efficiency of this cleavage is dependent on SLBP (Streit et al+, 1993;Dominski et al+, 1995)+ These considerations suggested that SLBP may contact the 39 flanking region FIGURE 5. A comparison of the consensus sequence of the histone mRNA 39 stem-loop with the specificity determinants for SLBP recognition+ Shown in gray boxes are nucleotides that show a deleterious effect on SLBP affinity when mutated or deleted+ and orient it for cleavage by the U7 snRNP+ We found, however, that much of the 39 flanking region could be deleted without a large effect on the affinity of the SLBP-RNA interaction (Fig+ 4)+ Deletion of four of the residues had only a slight effect, and deletion of the entire 39 flanking region increased the K d 5+5-fold+ This suggests that SLBP is not making extensive contacts to most of this region, but rather is only interacting with the first A residue 39 of the stem+ Alternatively, the presence of a 39 overhanging adenosine has been shown to contribute approximately 1 kcal/mol to the stability of short oligonucleotide duplexes (Freier et al+, 1986)+ It is possible, therefore, that A22 simply serves to stabilize the stem and is not contacting SLBP+ These data suggest that SLBP may enhance 39-end processing by direct or indirect recruitment of the U7 snRNP to the cleavage site as has been previously proposed (Dominski et al+, 1999), rather than by directly ordering the RNA structure at the cleavage site+ The sequence conservation of the 39 flanking region (and possibly the bottom G-C pair of the stem) may be necessary for the binding of other components of the 39-end processing machinery+ SLBP has no homology with any other proteins thus far discovered+ It contains a relatively small, approximately 73 amino acid, RNA-binding domain predicted to contain three a-helices (Wang et al+, 1996;Martin et al+, 2000)+ Previously characterized RNA-binding domains …”
Section: Discussionmentioning
confidence: 99%
“…A: Consensus secondary structure of the hammerhead numbered according to (Hertel et al+, 1992)+ The essential core nucleotides are designated in bold (H ϭ A, U, C and N ϭ nucleotide)+ The three loops (L1-L3) vary in length and sequence depending on where the hammerhead motif is embedded+ Arrow represents the site of cleavage 39 of position 17+ B: Three bimolecular formats of the hammerhead designated by the helices through which the substrate binds the ribozyme+ used+ Steps that have been proposed include: (1) conversion of E{S to a short-lived active complex with the attacking 29 oxygen positioned in line with the scissile phosphodiester bond (Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996; (2) a large conformational rearrangement that involves docking of the two domains of the catalytic core (Peracchi et al+, 1997); (3) a metal ion binding step (Long et al+, 1995); or (4) a conformational switch from an inactive E{S to an active E{S (Bassi et al+, 1995(Bassi et al+, , 1996+ It is well known that many RNA sequences can adopt multiple alternate structures that are as stable as the native structure (Herschlag, 1995;Uhlenbeck, 1995)+ The addition of a single alternate equilibrium involving one of the species of the minimal hammerhead kinetic pathway can alter the kinetics of cleavage in several different ways+ Both the rate of exchange and the overall equilibrium between the native and alternate structure can significantly alter the kinetic properties of the cleavage reaction+ To give just one example, consider a situation in which an alternate conformation of E{S, termed [E{S]9, forms off of the main pathway (Fig+ 3A)+ If the exchange rate is slow relative to the rate constant for cleavage (k 2 ) and the equilibrium constant results in, say, 40% of the complex being [E{S]9, the cleavage reaction will be biphasic with a fast rate, k 2 , up to 60% product, followed by a slow rate reflecting the conversion of [E{S]9 to E{S+ Very different behavior exists when the exchange rate is fast with respect to k 2 + As before, the amount of active E{S available for conversion to E{P1{P2 is reduced by the fraction of [E{S]9 formed at equilibrium, however, a single, slower rate of cleavage will be observed that equals (k conf 9/k conf )k 2 + Many other possible scenarios involving alternate structures can exist (Fig+ 3B,C,D) and these species are not always easy to detect+ The challenge is therefore to uncover these additional steps and to kinetically distinguish them from the steps of the minimal kinetic pathway+ The easiest hammerheads to work with are obviously those that do not have alternate conformations of the reaction species+ Several of these kinetically well-behaved or ideal hammerheads have been identified and steps can be taken to test whether sequences show such behavior (Fedor & Uhlenbeck, 1990, 1992Heus et al+, 1990;Hertel et al+, 1994;Clouetd'Orval & Uhlenbeck, 1996)+ Kinetically w...…”
Section: The Hammerhead Kinetic Pathway-an Overviewmentioning
confidence: 99%
“…The hammerhead ribozyme is a small RNA motif that self cleaves at a specific phosphodiester bond to produce 29,39 cyclic phosphate and 59 hydroxyl termini (Hutchins et al+, 1986;Forster & Symons, 1987a)+ The secondary structure of the hammerhead consists of three helices of arbitrary sequence and length (designated I, II, and III) that intersect at 15 nucleotides termed the catalytic core (Fig+ 1A) (Forster & Symons, 1987b;Hertel et al+, 1992)+ The X-ray crystal structures of two hammerhead ribozyme-inhibitor complexes revealed that the core residues fold into two separate domains and the helices are arranged in a Y-shape conformation with helix I and helix II forming the upper portion of the Y (Pley et al+, 1994;Scott et al+, 1995)+ Although the hammerhead is found as an intramolecular motif embedded in several RNAs in vivo (Symons, 1989), it can be assembled from two separate oligonucleotides (Fig+ 1B) in three different arrangements (Uhlenbeck, 1987;Haseloff & Gerlach, 1988;Koizumi et al+, 1988;Jeffries & Symons, 1989)+ In these bimolecular formats, the hammerhead effects RNA cleavage in a similar manner to a true "enzyme," proceeding through multiple rounds of substrate binding, cleavage, and product release (Uhlenbeck, 1987)+ Because of its relatively small size, ease of synthesis, and its well-described structure and cleavage properties, the hammerhead has been useful for studying many facets of RNA structure and function+ The major focus has been on understanding the mechanism by which the hammerhead catalyzes RNA cleavage+ The role of specific functional groups in either binding or catalysis has been probed by incorporation of both natural and modified nucleotides into the core of the hammerhead (Bratty et al+, 1993;Tuschl et al+, 1995;McKay, 1996;Chartrand et al+, 1997)+ In addition, the importance of metal ions in mediating cleavage has been studied extensively with the aim of establishing their roles in folding and catalysis (Dahm & Uhlenbeck, 1991;Perreault et al+, 1991;Dahm et al+, 1993;Grasby et al+, 1993;Menger et al+, 1996;Peracchi et al+, 1997;Feig et al+, 1998)+ The hammerhead ribozyme has also been used for the calibration of methods to probe more general properties of RNA such as folding and dynamics+ These methods include a gel mobility shift assay (Bassi et al+, 1995...…”
Section: Introductionmentioning
confidence: 99%
“…14 Interaction between a GNRA tetraloop and a helical stem was also noted in the hammerhead ribozyme crystal structure [1].…”
Section: Gaaa Tetraloop-receptor Interactionmentioning
confidence: 87%
“…The past decade has seen a vast increase in structural data on complex tertiary structures of RNA, beginning with the hammerhead ribozyme [1][2] and culminating in the atomic resolution structures of both the small (30S) [3][4] and large (50S) [5] ribosomal subunits. The recently published 5.5Å structure of the complete (70S) ribosome [6] indicates that this trend is likely to continue.…”
Section: Introductionmentioning
confidence: 99%